Challenges in implementing CLT at secondary schools in rural Bangladesh - Alam, Md Morshedul (IIUC Studies, 2018)
This paper tries to identify the factors that hinder implementing Communicative Language Teaching (CLT) in the secondary schools in rural Bangladesh. This article takes a qualitative approach, and it is carried out in four rural schools in Banskhali, which is situated in Chittagong district in Bangladesh. Eight secondary level English language teachers were interviewed to generate data about the problems in implementing CLT in their respective institutions. The findings indicate several challenges that include: shortage of skilled teachers, unusually large class size, deficiency of modern materials used in CLT oriented classrooms, etc. This research may provide implications for the language policy makers and the practitioners for the improvement of CLT practices in the rural contexts of Bangladesh. IIUC Studies Vol.13 December 2016: 93-102